2016
DOI: 10.6018/eglobal.16.1.237361
|View full text |Cite
|
Sign up to set email alerts
|

Terapia tópica para feridas crônicas: contribuições de um módulo de ensino à distância para o conhecimento de estudantes de enfermagem

Abstract: Estudio cuasi experimental tuvo como objetivo evaluar el desempeño de estudiantes de enfermería en test de conocimiento antes y después de participar en un módulo de enseñanza a distancia sobre terapia tópica para heridas crónicas utilizando Ambiente Virtual de Aprendizaje (AVA-Moodle). Desarrollado en tres etapas: aplicación del pre-test, implementación de la intervención en AVA-Moodle y aplicación del post-test. Participaron 37 estudiantes en el último año del Curso en Enfermería de Institución Pública de En… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 12 publications
0
6
0
3
Order By: Relevance
“…The benefits of active participation of the individual and the sexual partnership for the success of the actions were also emphasized. Unit VII -References and credits (8)(9)(10)(11)(12)(13)(14) .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The benefits of active participation of the individual and the sexual partnership for the success of the actions were also emphasized. Unit VII -References and credits (8)(9)(10)(11)(12)(13)(14) .…”
Section: Resultsmentioning
confidence: 99%
“…In this sense, the health professional, especially the nurse, has many benefits for being inserted in several services of the health care network, with the possibility of acting to raise awareness and promote behavior change in these individuals and adherence to the follow-up / treatment of syphilis (9) . Among the duties of the nurse, the potential to develop educational activities in order to awaken the desire for transformation and improvement in the quality of life of users, families and communities, based on the sharing of experiences, especially in the context of Primary Health Care (PHC), a priority site for the prevention, diagnosis and treatment of syphilis is highlighted (8)(9)(10) .…”
Section: Introductionmentioning
confidence: 99%
“…As for the construction process of the educational program through the TelEduc platform, it is observed that, in a study carried out in São Paulo, the authors highlighted the need to re-adjust TelEduc regarding the presentation format and digital media resources after expert analysis (19) .…”
Section: Discussion Category 1 -Use Of Virtual Technologies For Distamentioning
confidence: 99%
“…The goal is to make teaching more dynamic, attractive, interactive and enable the development of student autonomy. [31][32][33][34] We note that this research was limited as it involved only information and communication technology in nursing education and not in other healthcare areas, which could have increased the sample number and perhaps even diversified the findings. It is possible that if the inclusion criteria of the studies allowed including other areas of healthcare such as: Nursing Medicine, Occupational Therapy, Physical Education, Nutrition, Psychology, among others, it could have brought broader contributions and allowed reflection on other issues.…”
Section: Object and Virtual Learning Environment: Construction Of Newmentioning
confidence: 99%